Dissolução parcial de sociedade profissional - Armani, Wagner José Penereiro (2017)
This study intends to analyze the professional society that is constituted to provide the common exercise of intellectual or regulated profession. The Brazilian Constitution grants not only to the liberty of initiative of the entrepreneurs, but also to other professionals who may be engaged in the exercise of economic activity, including intellectual professionals and societies. This study will show the specific characteristics of the professional society and the implications of these specificities in the case of partial dissolution and the consequent determination of assets to quantify the value due to the member who leaves, for any reason, from a professional society. And this is where the professional society gains relevance, because the treatment given to it nowadays, in a mistaken way, deprives it of its organizational character and, therefore, also the possibility of being a holder of immaterial goods and compensation, harming eventual partner who leaves the society. This discussion gained new ground with the validity of the current Brazilian Civil Procedure Code, on March 18, 2016, and substantially modified the institute of partial dissolution of society. Accurate analysis of doctrine, academic material, legislation, jurisprudence, statistics, and practical cases has proven to be a method capable of pursuing a critical examination of the institute, seeking to give it a new meaning. It is concluded, therefore, that, depending on the organizational form of the professional society, there may be objective elements that value the business, there being no legal impediment to exclude intangible assets and the assessment of the valuation made in the determination of assets of the member that leaves from Professional society